2014
DOI: 10.1007/s12223-014-0323-5
|View full text |Cite
|
Sign up to set email alerts
|

C. difficile ribotype 027 or 176?

Abstract: Clostridium difficile is a major nosocomial pathogen of present times. The analysis of 624 C. difficile strains from 11 hospitals in the Czech Republic in 2013 revealed that 40% of isolates belonged to ribotype 176. These results suggest that the incidence of CDI (C. difficile infection) in the Czech Republic has increased probably in connection with C. difficile ribotype 176. The molecular systems Xpert C. difficile Epi assay (Cepheid Inc., Sunnyvale, CA) diagnoses toxigenic strains and supports C. difficile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 5 publications
0
21
1
Order By: Relevance
“…Clostridium difficile ribotype 176 may be misinterpreted as ribotype 027 by GeneXpert ® C. difficile (Cepheid). Therefore, further molecular analysis such as ribotyping based on capillary electrophoresis is needed to better differentiate between C. difficile ribotypes 027 and 176 such that appropriate steps can be taken at the local and national levels to prevent outbreaks (28). In many places, C. difficile surveillance is not yet sufficient; thus, the number of outbreaks is increasing.…”
Section: Discussionmentioning
confidence: 99%
“…Clostridium difficile ribotype 176 may be misinterpreted as ribotype 027 by GeneXpert ® C. difficile (Cepheid). Therefore, further molecular analysis such as ribotyping based on capillary electrophoresis is needed to better differentiate between C. difficile ribotypes 027 and 176 such that appropriate steps can be taken at the local and national levels to prevent outbreaks (28). In many places, C. difficile surveillance is not yet sufficient; thus, the number of outbreaks is increasing.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, shortly afterward the 2008 study, the occurrence of ribotype 176 was reported in certain areas of the country (Eastern Bohemia and Moravia) [9]. This ribotype has persisted in the Czech Republic [8] and was also reported in Poland in 2008-13, which borders the country [10,11].…”
Section: Introductionmentioning
confidence: 98%
“…Ribotype 176 is closely related to 027 [6,7] and can be misidentified by commercial tests targeting a singlebase-pair deletion at nucleotide 117 in the C. difficiletcdC gene [8]. In 2009, shortly afterward the 2008 study, the occurrence of ribotype 176 was reported in certain areas of the country (Eastern Bohemia and Moravia) [9].…”
Section: Introductionmentioning
confidence: 99%
“…(clade 2), as was published by Knetsch et al (Knetsch et al, 2012), as well as the presence of one base pair deletion at nucleotide position 117, which is a target site for commercial molecular systems (Krutova et al, 2014a;Mentula et al, 2015), (except WRT 413) as previously described above revealed a nonsense mutation C184T (Spigaglia and Mastrantonio, 2002;Curry et al, 2007). All these isolates (RT 023,027,126,176 and WRTs 413 and 438) revealed the presence of binary toxin genes, another important C. difficile virulence factor (Gerding et al, 2014).…”
Section: Discussionmentioning
confidence: 64%